Rectangular slot antenna with Asymmetrical conductor strip for bandwidth enhancement coverage UWB standard - Archevapanich, Tuanjai; Rakluea, Paitoon; Anantrasirichai, Noppin; Purahong, Boonchana; Chutchavong, Vanvisa (My University, 2014)
This paper presents the bandwidth enhancement of rectangular slot antenna fed by microstrip line on the flexible Mylar Polyester film substrate. Asymmetrical conductor strip is designed and inserted in the rectangular slot to extend the bandwidth from 3.06 GHz to 7.2 GHz frequency range. Besides, the rectangular conductor at the end of the feeding microstrip line is introduced for increasing the bandwidth at high frequency up to 12.32 GHz. This improved antenna to cover standard frequency range of UWB (3.1 GHz – 10.6 GHz). Finally, as to reject the frequency band of IEEE 802.11a (5.15 GHz – 5.35 GHz), the line strip at the side of tuning stub is added. In this case, the band-notched frequency from 5.15GHz to 5.38 GHz can be easily obtained.
Keywords: Asymmetrical conductor strip; Band-notched; Film substrate; Slot antenna; Tuning stub; UWB